Performance of Rigid and Soft Transfer Templates Using Viscous and Fluid Resin-Based Composites in the Attachment Bonding Process of Clear Aligners - Cristina Valeri; Angelo Aloisio; Stefano Mummolo; Vincenzo Quinzi (Hindawi Limited, 2022)
Objectives. The study aims at assessing the accuracy of the process of attachment bonding in aligner treatments. The analysis leads to the error estimation in the faithful reproduction of master model attachments using two types of transfer templates and two light-curing resin-based composites usually used in orthodontics. Methods. The authors have used two transfer templates made of two different materials. The first, named Leone-biocompatible thermoforming material hard/soft, has a lower Young's modulus and is labelled as soft, while the other, named Leone-biocompatible thermoforming material, is marked as rigid. The resin-based composites possess different mechanical and rheological properties. Specifically, Transbond™ XT Light Cure Paste Adhesive, 3M has a higher viscosity than the TetricEvoflow, Ivoclar Vivadent, a flowable nanohybrid composite. The authors attempt to estimate the performance ranking between the four possible couples obtained by combining the two light-curing resin-based composites and transfer templates. Each combination was repeated in six models and compared with twelve master models, resulting in 36 total samples. A 3-D laser scanner is used to generate a digital model of each model. The comparison between digital models is the base for a comparative assessment in terms of relative and absolute error. The relative error is estimated using scalar performance indicators ranging from 0 to 1, where 1 indicates the optimum matching. The absolute error estimated from the mean square error between the coordinates of each digital model yields the reproduction accuracy in micrometer. Furthermore, the authors attempted to assess the error distribution by evaluating the point-by-point difference between the digital models. Results. This analysis aims at localizing the sources of error in the considered models. The use of Transbond™ XT Light Cure Paste Adhesive, 3M with a rigid transfer template is always associated with significant accuracy and minor dispersion. However, in a few instances, using the soft template or the flowable resin-based composite can lead to bad performances. Significance. The data processing bestowed the following performance ranking from the first with lower reproduction error to the last characterized by the worst performance: (1) attachments bonding with rigid template and Transbond™ XT Light Cure Paste Adhesive, 3M, (2) attachments bonding with soft template and Transbond™ XT Light Cure Paste Adhesive, 3M, (3) attachments bonding with rigid template and TetricEvoflow, Ivoclar Vivadent, and (4) attachments bonding with soft template and TetricEvoflow, Ivoclar Vivadent.